Live Attenuated Tularemia Vaccines for Protection Against Respiratory Challenge With Virulent F. tularensis subsp. tularensis - Jia, Qingmei; Horwitz, Marcus A. (Frontiers in Cellular and Infection Microbiology, 2018)
Francisella tularensis is the causative agent of tularemia and a Tier I bioterrorism agent. In the 1900s, several vaccines were developed against tularemia including the killed “Foshay” vaccine, subunit vaccines comprising F.tularensis protein(s) or lipoproteins(s) in an adjuvant formulation, and the F.tularensis Live Vaccine Strain (LVS); none were licensed in the U.S.A. or European Union. The LVS vaccine retains toxicity in humans and animals – especially mice – but has demonstrated efficacy in humans, and thus serves as the current gold standard for vaccine efficacy studies. The U.S.A. 2001 anthrax bioterrorism attack spawned renewed interest in vaccines against potential biowarfare agents including F.tularensis. Since live attenuated – but not killed or subunit – vaccines have shown promising efficacy and since vaccine efficacy against respiratory challenge with less virulent subspecies holarctica or F.novicida, or against non-respiratory challenge with virulent subsp. tularensis (Type A) does not reliably predict vaccine efficacy against respiratory challenge with virulent subsp. tularensis, the route of transmission and species of greatest concern in a bioterrorist attack, in this review, we focus on live attenuated tularemia vaccine candidates tested against respiratory challenge with virulent Type A strains, including homologous vaccines derived from mutants of subsp. holarctica, F.novicida, and subsp. tularensis, and heterologous vaccines developed using viral or bacterial vectors to express F. tularensis immunoprotective antigens. We compare the virulence and efficacy of these vaccine candidates with that of LVS and discuss factors that can significantly impact the development and evaluation of live attenuated tularemia vaccines. Several vaccines meet what we would consider the minimum criteria for vaccines to go forward into clinical development – safety greater than LVS and efficacy at least as great as LVS, and of these, several meet the higher standard of having efficacy ≥LVS in the demanding mouse model of tularemia. These latter include LVS with deletions in purMCD, sodBFt, capB or wzy; LVS capB that also overexpresses Type VI Secretion System (T6SS) proteins; FSC200 with a deletion in clpB; the single deletional purMCD mutant of F.tularensis SCHU S4, and a heterologous prime-boost vaccine comprising LVS capB and Listeria monocytogenes expressing T6SS proteins.